The COVID-19 Pandemic Affects Intellectual Capital on the Financial Performance of Pharmaceutical Companies in Indonesia - Yerisma Welly; Andri Zainal; Marto Silalahi; Martin Yehezkiel Sianipar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to examine the effect of Intellectual Capital (IC) on the financial performance of Return On Equity (ROE) of companies in the pharmaceutical sub sector. The population in this study is the financial statements of companies in the pharmaceutical sub sector listed on the Indonesian Stock Exchange during the 2017-2021 period. This study used purposive sampling with 8 companies and 40 observations. This study used quantitative data. Data collection techniques using documentation techniques. Data analysis techniques used in this research are classic assumption test, simple linear regression, F test and t test using the SPSS 21 version as a data processing program. The results showed that the intellectual capital had a positive and significant effect on financial performance. This finding indicates that the more efficient and effective a company is in managing its IC, the more it will improve the company's financial performance. The company's ability to generate profit with the total equity owned by the company is increasing with the company using and making the most of its IC. So this research proves that IC plays an important role in the formation of added value and contributes to improving the company's financial performance. This finding also confirms the resource based theory, that intellectual capital owned by companies is able to create competitive advantages for companies so that they can improve company performance for the better, one of which is increasing company profits.